Forensic engineering of advanced polymeric materials. Part III - Biodegradation of thermoformed rigid PLA packaging under industrial composting conditions. (June 2016) - Musioł, Marta; Sikorska, Wanda; Adamus, Grazyna; Janeczek, Henryk; Richert, Jozef; Malinowski, Rafal; Jiang, Guozhan; Kowalczuk, Marek
Highlights: Thermal processing has little effect on the degradation behaviour of PLA. The control of moisture and temperature is important factors that affect the degradation of PLA. The molecular mass distributions of PLA during degradation show a bimodal profile. Abstract: This paper presents a forensic engineering study on the biodegradation behaviour of prototype packaging thermoformed from PLA-extruded film and plain PLA film under industrial composting conditions. Hydrolytic degradation in water was conducted for reference. The effects of composting duration on changes in molar mass, glass transition temperature and degree of crystallinity of the polymeric material were monitored using gel permeation chromatography (GPC) and differential scanning calorimetry (DSC). The chemical structure of water soluble degradation products of the polymeric material was determined using nuclear magnetic resonance (NMR) and electrospray ionization mass spectrometry (ESI-MS). The results show that the biodegradation process is less dependent on the thermoforming process of PLA and more dependent on the composting/degradation conditions that are applied. The increase in the dispersity index, leading to the bimodal molar mass distribution profile, suggests an autocatalytic hydrolysis effect at the early stage of the composting process, during which the bulk hydrolysis mechanism dominantly operates. Both the prototype PLA-packaging and PLA rigid film samples were shown to have a gradual increase in opacity due to an increase in the degree of crystallinity.